A Fast Method for DEFB1-44C/G SNP Genotyping in Brazilian Patients with Periodontitis - Renata Cimões; Rafael Rafael Amorim Cavalcanti de Siqueira; Sergio Crovella; Paulo Roberto Eleutério de Souza; Nikos Donos (University of Zagreb. School of Dental Medicine, 2014)
Aim: Defensins are cationic antimicrobial peptides expressed in epithelial cells. Such peptides exhibit antibacterial, antifungal and antiviral properties, and are a component of the innate immune response. It has been suggested that they have a protective role in the oral cavity. This study evaluated the DEFB1 polymorphism in diabetic patients with or without periodontitis in comparison to healthy controls. Material and Methods: We used Hairpin-Shaped Primer (HP) assay to study the distribution of the -44 C/G SNP (rs1800972) in 119 human DNAs obtained from diabetic patients and healthy control patients. Results: The results indicate that there are no differences in distribution between groups and that in diabetic periodontitis patients the homozygous mutant could be found more frequently. Conclusion: Further studies are necessary in order to investigate the role of DEFB1 polymorphisms in diabetic periodontitis patients and the influence of the peptide in periodontal pathogens.